2011
DOI: 10.1177/0022034511431251
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytical Review of Parameters Involved in Dentin Bonding

Abstract: Bond-strength testing is the method most used for the assessment of bonding effectiveness to enamel and dentin. We aimed to disclose general trends in adhesive performance by collecting dentin bond-strength data systematically. The PubMed and EMBASE databases were used to identify 2,157 bond-strength tests in 298 papers. Most used was the micro-tensile test, which appeared to have a larger discriminative power than the traditional macro-shear test. Because of the huge variability in dentin bond-strength data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
134
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(157 citation statements)
references
References 38 publications
9
134
1
13
Order By: Relevance
“…We performed a broad search and a strict selection for meta-analysis to decrease heterogeneity of the data. In several of the analyses performed, there was high heterogeneity of the data (97%), corroborating the literature showing the wide range of bond strength values comparing in vitro studies (De Munck et al, 2012). However, that high heterogeneity occurred only for longitudinal (aging) meta-analysis, not immediate (without aging).…”
Section: Discussionsupporting
confidence: 80%
“…We performed a broad search and a strict selection for meta-analysis to decrease heterogeneity of the data. In several of the analyses performed, there was high heterogeneity of the data (97%), corroborating the literature showing the wide range of bond strength values comparing in vitro studies (De Munck et al, 2012). However, that high heterogeneity occurred only for longitudinal (aging) meta-analysis, not immediate (without aging).…”
Section: Discussionsupporting
confidence: 80%
“…While some authors found no significant effect on adhesion [31,32], others did [33,34]. Its effect on bond strength is contradictory and seems to depend on the number of cycles [35,36], size of the specimens [36,37] and the C-factor [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for failure of restorations on the long-term are fracture and secondary caries 1) . Considering the high turnover of new materials on the market, it is important to test these materials first in vitro in a clinical relevant way, in order to be able to predict possible clinical pathways of failure 2,3) . Therefore, aging processes resembling those taking place in the oral environment were introduced in laboratory testing procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of thermal and mechanical stresses have been used to try to reproduce these conditions. However, the popular thermal cycling method has limited effect compared to mechanical aging 3) . Mechanical load cycles and forces applied are not standard in most studies, as well as methods and devices used to apply the force 4,5) .…”
Section: Introductionmentioning
confidence: 99%